2000
DOI: 10.1128/jvi.74.1.436-446.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Novel K15 Gene at the Rightmost End of the Kaposi's Sarcoma-Associated Herpesvirus Genome

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) encodes a distinct open reading frame called K15 at a position equivalent to the gene encoding LMP2A of Epstein-Barr virus (EBV). K15 isolates from body cavity-based lymphoma (BCBL) cells exhibited a dramatic sequence variation and a complex splicing pattern. However, all K15 alleles are organized similarly with the potential SH2 and SH3 binding motifs in their cytoplasmic regions. Northern blot analysis showed that K15 was weakly expressed in latently infected BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
157
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 38 publications
8
157
1
Order By: Relevance
“…We previously demonstrated that the cytoplasmic region of K15 inhibited the proximal signal transduction of BCR to cellular tyrosine phosphorylation and calcium mobilization. Based on these results, we hypothesized that K15 is not only a structural homolog but also a functional homolog to EBV LMP2A protein (Choi et al, 2000). However, detailed molecular mechanism remained unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that the cytoplasmic region of K15 inhibited the proximal signal transduction of BCR to cellular tyrosine phosphorylation and calcium mobilization. Based on these results, we hypothesized that K15 is not only a structural homolog but also a functional homolog to EBV LMP2A protein (Choi et al, 2000). However, detailed molecular mechanism remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of CD-delta ( = CD8-∆) and CD8-K15 chimera constructs is described in Choi et al (2000).…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…To do this, lymphotropic gammaherpesviruses, particularly Epstein-Barr virus, KSHV, and HVS, have been shown to deregulate lymphocyte signal transduction (8,27,34). Two HVS proteins, ORF14 and Tip, have been previously found to target and alter TCR signal transduction.…”
mentioning
confidence: 99%